Resveratrol and Neuroprotection: Impact and Its Therapeutic Potential in Alzheimer's Disease - Rahman, Md. Habibur; Akter, Rokeya; Bhattacharya, Tanima; Abdel-Daim, Mohamed M.; Alkahtani, Saad; Arafah, Mohammed W.; Al-Johani, Norah S.; Alhoshani, Norah M.; Alkeraishan, Nora; Alhenaky, Alhanof; Abd‐Elkader, Omar H.; El-Seedi, Hesham R; et al. (Frontiers in Pharmacology, 2020)
Alzheimer’s disease (AD) is a progressive cortex and hippocampal neurodegenerative disease which ultimately causes cognitively impaired patients. The AD pathogen is very complex, including aggregation of Aβ, phosphorylation of tau-proteins, chronic inflammation. Exactly, resveratrol, a polyphenol in red wine, and many plants are indicated to show the neuroprotective effect on mechanisms mostly above. Most experimental research on AD and resveratrol has been performed in many species, both in vitro and in vivo, during the last few years. Nevertheless, Resveratrol’s effects are restricted by its bioavailability in the reservoir. Therefore, scientists have tried to improve efficiency by different methods. This review draws together recent work on the cell and animal cultures, focuses on the neuroprotective molecular mechanisms of resveratrol, and also discusses the therapeutic potential on to the treatment of AD.